Convoluted maxillary stylets among Australian Thysanoptera Phlaeothripinae associated mainly with Casuarinaceae trees - Mound, Laurence A.; Tree, Desley J.; Wells, Alice (Zootaxa, 2022)
The diversity is reviewed of Phlaeothripinae in Australia with unusually long or convoluted maxillary stylets. This comprises a total of 28 species in eight genera, including Enigmathrips carnarvoni gen et sp.n., Adrothrips latrarei sp.n., A. lihongae sp.n., A. madiae sp.n., A mitcheli sp.n., A. vernoni sp.n., and A. westoni sp.n., also Heligmothrips exallus sp.n., H. macropus sp.n., H. narrabri sp.n. and H. xanthoskelus sp.n., and Iotatubothrips daguilari sp.n. Among Phlaeothripinae, such exceptionally long feeding stylets are known only from Australia and have evolved independently within the unrelated genera Adrothrips and Heligmothrips in association with the green branchlets of Casuarinaceae species. A few species appear to have diverged in their feeding habits and have adapted to fungal-hyphal feeding on the trunks of trees.